Investigating the relationship between UMODL1 gene polymorphisms and high myopia: a case-control study in Chinese - Zhu Miao-miao; Yap Maurice KH; Ho Daniel WH; Fung Wai Yan; Ng Po Wah; Gu Yang-shun; Yip Shea Ping (BMC, 2012)
Abstract Background The UMODL1 gene was found to be associated with high myopia in Japanese. This study aimed to investigate this gene for association with high myopia in Chinese. Methods Two groups of unrelated Han Chinese from Hong Kong were recruited using the same criteria: Sample Set 1 comprising 356 controls (spherical equivalent, SE, within ±1 diopter or D) and 356 cases (SE ≤ −8D), and Sample Set 2 comprising 394 controls and 526 cases. Fifty-nine tag single nucleotide polymorphisms (SNPs) were selected and genotyped for Sample Set 1. Four SNPs were followed up with Sample Set 2. Both single-marker and haplotype analyses were performed with cases defined by different SE thresholds. Secondary phenotypes were also analyzed for association with genotypes. Results Data filtering left 57 SNPs for analysis. Single-marker analysis did not reveal any significant differences between cases and controls in the initial study. However, haplotype GCT for markers rs220168-rs220170-rs11911271 showed marginal significance (empirical P = 0.076; SE ≤ −12D for cases), but could not be replicated in the follow-up study. In contrast, non-synonymous SNP rs3819142 was associated with high myopia (SE ≤ −10D) in the follow-up study, but could not be confirmed using Sample Set 1. The SNP rs2839471, positive in the original Japanese study, gave negative results in all our analyses. Exploratory analysis of secondary phenotypes indicated that allele C of rs220120 was associated with anterior chamber depth (adjusted P = 0.0460). Conclusions Common UMODL1 polymorphisms were unlikely to be important in the genetic susceptibility to high myopia in Han Chinese.